2017
DOI: 10.1016/j.hemonc.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation in the Sultanate of Oman

Abstract: The Sultanate of Oman is one of the Arabian Gulf countries with a total population of 4,414,051 as of mid 2016, of which 2,427,825 are Omanis. The gross national income per capita was 7327.7 RO (Omani rial; equivalent to US$19,033) in 2014. There are two hematopoietic stem cell transplantation (HSCT) centers in Oman: the Sultan Qaboos University Hospital (SQUH; allogeneic and autologous) and the Royal Hospital (RH; autologous). HSCT activity in Oman started in 1995 at the SQUH center, which had only one bed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…No significant relationship was found between the area of residence and OS as assessed by the Cox regression analysis. Additionally, Omani patients receiving HSCT are generally younger than those reported in studies from Europe and North America 8. Therefore, the association between DTC and OS may not be as strong in younger patients when compared to older patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…No significant relationship was found between the area of residence and OS as assessed by the Cox regression analysis. Additionally, Omani patients receiving HSCT are generally younger than those reported in studies from Europe and North America 8. Therefore, the association between DTC and OS may not be as strong in younger patients when compared to older patients.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, data suggests that an increase in DTC is not associated with the development of aGvHD ( P = 0.918). Al-Khabori et al .’s study showed that the incidence of aGvHD in patients transplanted at SQUH was 32% while the incidence of chronic GvHD was 16% 8. Similar reasons as for the OS outcome could also be applicable for the aGvHD outcome.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 2 In Oman, nearly half of the cases that require transplantation are inherited. 3 Following the worldwide trend, hematopoietic stem cell transplantation (HSCT) is being increasingly preferred in Oman and its neighboring countries, due to a greater likelihood of cure.…”
mentioning
confidence: 99%
“…About 2/3rd are allotransplants and 1/3rd is autotransplants. The combined rate of 2-2.5/10 × 10E + 5 population is like other Arab countries in the Middle East but about fivefold lower than the EU and US [4][5][6][7][8][9]. Adjusting for the high proportion of allotransplants to autotransplants the respective rates are about three to tenfold lower than the US and EU.…”
mentioning
confidence: 99%